Pigmented Lesions Of Nonmelanocytic Origin A Pathological Perspective - Crasta Julian; Rameshkumar Karuna (Wolters Kluwer Medknow Publications, 2002)
Many Pigmented lesions of nonmelanocytic origin can mimic clinically melanocytic lesions including malignant melanoma. A histological interpretation by pathology is helpful in the diagnosis and management of these lesions. The cases during a two year period from January 1999 to December 2000 were reviewed to assess the prevalence of lesions with pigmented variants where histopathological examination helped to confirm/refute the clinical diagnosis. The most common lesion presented with such diagnostic difficulty clinically was seborrhoeic keratosis. Other lesions observed in the study included basal cell carcinoma (12), actinic keratosis (3) and dermatofibrosarcoma protuberans (3). The total number of cases studied was 26. Adherence to strict diagnostic criteria helped towards the correct diagnosis. As 50% of the lesions had pigmentation and 30% had a clinical diagnosis of melanoma, histopathologic evolution was crucial to avoid overdiagnosis of melanoma and to provide reassurance in benign lesions.